Bioprinted Injectable Hierarchically Porous Gelatin Methacryloyl Hydrogel Constructs with Shape‐Memory Properties. (6th September 2020) - Ying, Guoliang; Jiang, Nan; Parra‐Cantu, Carolina; Tang, Guosheng; Zhang, Jingyi; Wang, Hongjun; Chen, Shixuan; Huang, Ning‐Ping; Xie, Jingwei; Zhang, Yu Shrike
Abstract: Direct injection of cell‐laden hydrogels shows high potential for tissue regeneration in translational therapy. The traditional cell‐laden hydrogels are often used as bulk space fillers to tissue defects after injection, likely limiting their structural controllability. On the other hand, patterned cell‐laden hydrogel constructs often necessitate invasive surgical procedures. To overcome these problems, herein, a unique strategy is reported for encapsulating living human cells in a pore‐forming gelatin methacryloyl (GelMA)‐based bioink to ultimately produce injectable hierarchically macro‐micro‐nanoporous cell‐laden GelMA hydrogel constructs through 3D extrusion bioprinting. The hydrogel constructs can be fabricated into various shapes and sizes that are defect‐specific. Due to the hierarchically macro‐micro‐nanoporous structures, the cell‐laden hydrogel constructs can readily recover to their original shapes, and sustain high cell viability, proliferation, spreading, and differentiation after compression and injection. In addition, in vivo studies further reveal that the hydrogel constructs can integrate well with the surrounding host tissues. These findings suggest that the unique 3D‐bioprinted pore‐forming GelMA hydrogel constructs are promising candidates for applications in minimally invasive tissue regeneration and cell therapy. Abstract : An aqueous two‐phase emulsion bioink is used to fabricate a hierarchically macro‐micro‐nanoporous cell‐laden gelatin methacryloyl hydrogel constructs via 3D extrusion bioprinting. A variety of shapes and sizes of the hydrogel constructs can be minimally invasively injected, and readily shape‐recovered to fill irregular defects. The encapsulated cells maintain their viabilities, proliferation, spreading, and differentiation after injection.